Initial Output Losses from the Covid-19 Pandemic : Robust Determinants. (Washington, D.C. : International Monetary Fund, 2021)
While the COVID-19 pandemic is affecting all countries, output losses vary considerably across countries. We provide a first analysis of robust determinants of observed initial output losses using model-averaging techniques-Weighted Average Least Squares and Bayesian Model Averaging. The results suggest that countries that experienced larger output losses are those with lower GDP per capita, more stringent containment measures, higher deaths per capita, higher tourism dependence, more liberalized financial markets, higher pre-crisis growth, lower fiscal stimulus, higher ethnic and religious fractionalization and more democratic regimes. With respect to the first factor, lower resilience of poorer countries reflects the higher economic costs of containment measures and deaths in such countries and less effective fiscal and monetary policy stimulus.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet